A new flesh fly species (Diptera: Sarcophagidae) parasitic on leptodactylid frogs - Mulieri, Pablo Ricardo (2018)
Here we describe a new species of sarcophagid fly reared from larvae found feeding on three species of leptodactylid frogs collected in subtropical Corrientes Province in northeastern Argentina. Our species description is based on adult male and female external morphology and genitalia. Adult males and females of the new species were associated with certainty because all specimens studied were reared from single clutches of larvae on each of three infested frogs. Thus, adult males and females reared from each clutch were siblings that emerged almost simultaneously. The paper provides line drawings, high-resolution photographs, and SEM images to aid in identifying Lepidodexia (Notochaeta) adelinasp. nov. and to distinguish the new species from its closely related congeners. We include brief notes on the host species and on larval feeding behavior of L. (N.) adelina. This is the first and only species in the genus Lepidodexia reported to parasitize leptodactylid frogs. Further, our observations reported here are the first to fully document a completed life cycle by sarcophagid fly larvae on three different species of leptodactylid frogs and the only well-documented case of myiasis of an amphibian in Argentina.